2018
DOI: 10.1016/j.devcel.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response and Off-Target Mis-splicing Are Common Morpholino-Induced Side Effects in Xenopus

Abstract: SummaryAntisense morpholino oligomers (MOs) have been indispensable tools for developmental biologists to transiently knock down (KD) genes rather than to knock them out (KO). Here we report on the implications of genetic KO versus MO-mediated KD of the mesoderm-specifying Brachyury paralogs in the frog Xenopus tropicalis. While both KO and KD embryos fail to activate the same core gene regulatory network, resulting in virtually identical morphological defects, embryos injected with control or target MOs also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 92 publications
(137 reference statements)
4
37
0
Order By: Relevance
“…While research shows that morpholino-induced phenotypes can be the result of off-target effects (Robu et al, 2007;Gentsch et al, 2018;Kok et al, 2015), fully established and validated morpholinos are generally accepted . They offer the ability to knock down gene expression in any zebrafish line without the maintenance of a transgenic or mutant background, but they do not offer much temporal control or long-term knockdown.…”
Section: Macrophagesmentioning
confidence: 99%
“…While research shows that morpholino-induced phenotypes can be the result of off-target effects (Robu et al, 2007;Gentsch et al, 2018;Kok et al, 2015), fully established and validated morpholinos are generally accepted . They offer the ability to knock down gene expression in any zebrafish line without the maintenance of a transgenic or mutant background, but they do not offer much temporal control or long-term knockdown.…”
Section: Macrophagesmentioning
confidence: 99%
“…One major cause of these effects is the activation of p53mediated apoptosis, which can be attenuated by co-injection of a morpholino that targets the p53 gene (Robu et al, 2007). In addition to p53 activation, evidence from Xenopus tropicalis has demonstrated widespread regulation of non-target genes, primarily those with immune function, and mis-splicing of non-target genes in response to morpholino injection (Gentsch et al, 2018). Indeed, there is now mounting evidence, derived primarily from zebrafish, that morphants often do not phenocopy null mutants (Robu et al, 2007;Gerety and Wilkinson, 2011;Kok et al, 2015;Novodvorsky et al, 2015;Rossi et al, 2015;Shmukler et al, 2015;Eve et al, 2017;Joris et al, 2017).…”
Section: Morpholino Antisense Oligonucleotidesmentioning
confidence: 99%
“…Importantly, the lack of overt phenotype at the 4 ng dose does not necessarily imply that this morpholino was free of off-target effects. For both morpholinos and RNAi, studies have demonstrated widespread regulation of non-target genes thought to be related to immune responses, splice defects or promiscuous binding in the case of morpholinos (Joris et al, 2017;Gentsch et al, 2018) or to alteration of miRNA pathways by shRNA (Baek et al, 2014). It is possible that these sub-phenotypic effects can have confounding effects on the interpretation of knockdown results.…”
Section: Dose-specific Off-target Effectsmentioning
confidence: 99%
“…Controls include the use of more than one MO, dose dependency, and rescue of phenotypes by co-injecting rescue mRNAs that are not targeted by the MO. The debate on specificities of gene and mRNA targeting is old and ongoing and should remind every researcher to remain critical and careful when interpreting a specific result [Eisen and Smith, 2008;Blum et al, 2015;Kok et al, 2015;Moulton, 2017;Gentsch et al, 2018]. In Xenopus, genome editing by the CRISPR/Cas9 technology is easily performed and can serve to validate the use of MOs, as well as being utilized as a valid genetic tool in its own rights [Garfinkel and Khokha, 2017;Naert et al, 2017;Tandon et al, 2017;Blitz, 2018;Naert and Vleminckx, 2018].…”
Section: The African Frog Xenopusmentioning
confidence: 99%